2005
DOI: 10.1111/j.1365-2354.2005.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with cancer in non-specialist wards: the nurse experience

Abstract: This study aims to describe the experiences of nurses caring for cancer patients in non-specialist wards. The study was conducted in a large (420 beds) and small (32 beds) hospital in an area health service with urban and rural populations in the west of Sydney. A qualitative descriptive approach was utilized to collect data from the nurses. Data were collected using a survey and in-depth interviews of nurses working in non-specialist cancer wards. Transcribed data were managed with Nudist Vivo software and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 25 publications
3
50
0
4
Order By: Relevance
“…The particular finding is similar with the results of a study by Mohan et al (2005) which compared urban and rural population in Sydney, Australia. They reported that the provision of the nursing care, for patients with cancer and their families at non-specialist hospital ward setting, was confronting and emotionally draining.…”
Section: Level Of Patients' Satisfaction According To University's Hosupporting
confidence: 81%
“…The particular finding is similar with the results of a study by Mohan et al (2005) which compared urban and rural population in Sydney, Australia. They reported that the provision of the nursing care, for patients with cancer and their families at non-specialist hospital ward setting, was confronting and emotionally draining.…”
Section: Level Of Patients' Satisfaction According To University's Hosupporting
confidence: 81%
“…Four discourses have been observed on hospital wards' caring, noncaring, curing, and organization that incorporates nursing in the medically dominated context and limits the development of nursing care-related core tasks (Dahlborg-Lyckhage & Lidén, 2010). From a nursing perspective, the conditions for providing palliative care on a hospital ward are perceived as being restrictive and also characterized by nurses' insufficient knowledge about cancer treatment, lack of competence to provide psychosocial support to the patient and family, being overworked, and an inappropriate physical environment (Gill & Duffy, 2010;Mohan, Wilkes, Ogunsiji, & Walker, 2005). Nurses deal with these factors by allocating time to direct patient care based on a prioritization of what they perceive as quality levels of nursing, defined as "selective focusing" (Williams, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…[28][29][30] Both primary care nurses and family physicians are caring for most patients with advanced cancer, [14][15][16][17][18]27 and referral for radiotherapy is made when it is considered to be required. Health care professionals making referrals can benefit from knowledge of effective options for the treatment of oncologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although most referrals come through physicians, nurses are often involved in the day-to-day care of patients with advanced cancer, whether in patients' homes, nursing homes, or palliative care facilities. [16][17][18] Facilitating good communication between physicians and nurses would likely increase referral for PR once an indication was identified by nursing staff. 19 It has previously been shown that knowledge and end-of-life care can be improved through palliative care education for both nurses and physicians.…”
mentioning
confidence: 99%